How to Build Plasmon-Driven Molecular Jackhammers that Disassemble Cell Membranes and Cytoskeletons in Cancer - Ayala-Orozco, Ciceron (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.